2020
DOI: 10.3390/ijms21239311
|View full text |Cite
|
Sign up to set email alerts
|

Methylation: An Ineluctable Biochemical and Physiological Process Essential to the Transmission of Life

Abstract: Methylation is a universal biochemical process which covalently adds methyl groups to a variety of molecular targets. It plays a critical role in two major global regulatory mechanisms, epigenetic modifications and imprinting, via methyl tagging on histones and DNA. During reproduction, the two genomes that unite to create a new individual are complementary but not equivalent. Methylation determines the complementary regulatory characteristics of male and female genomes. DNA methylation is executed by methyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 81 publications
(151 reference statements)
0
22
0
Order By: Relevance
“…In the bovine, MTHFR has been shown to regulate blastocyst development and viability, with an influence on cell number in both the inner cell mass and the trophoblast [27]. This confirms the role of methylation in blastocyst development and fetal development all along pregnancy [8]. Although determination of the 677CT isoform might be sufficient for screening, the 1298AC isoform, also associated with early human developmental anomalies [20,23,26] is also well represented.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the bovine, MTHFR has been shown to regulate blastocyst development and viability, with an influence on cell number in both the inner cell mass and the trophoblast [27]. This confirms the role of methylation in blastocyst development and fetal development all along pregnancy [8]. Although determination of the 677CT isoform might be sufficient for screening, the 1298AC isoform, also associated with early human developmental anomalies [20,23,26] is also well represented.…”
Section: Discussionmentioning
confidence: 81%
“…Methylation is required for the formation of thymine from uracil; defects may lead to DNA repair and genomic instability [6,7]. It is a mandatory process in transmission of life: it is a major regulator in gametogenesis, embryo development, and growth via, but only, its role in epigenesis and imprinting mechanisms [8]. Since excess Hcy and the presence of MTHFR SNPs increase pathology risks in general [9][10][11][12], the risk of infertility at all stages pre-and postconception [13][14][15][16][17][18], the frequency of miscarriage [6,19,20], and compromised infant health [21][22][23], we have determined retrospectively the prevalence of the two main MTHFR SNPs in our population of 2970 male and female patients consulting for infertility; serum homocysteine levels were assessed in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate endometriosis surgically treated, recurrent failed clomid stimulations, failed IUI, biochemical pregnancy and failed ART could not be overcome before treatment with 5-MTHF, the compound located downstream the MTHFR blockade. MTHFR SNP may lead, sooner or later to embryo developmental arrests [1,4,8,14]. This means that patients with endometriosis [11,12], a history of recurrent pregnancy losses, multiple failed IUIs or failed ART should be tested for MTHFR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…MTHFR, located on the short arm of chromosome 1, catalyses the reduction of 5,10 methylenetetrahydrofolate to 5-methytetrahydrofolate, and is used for cellular methylation processes including epigenetic and imprinting regulation via DNA and histone methyl tagging. These two cycles play a major role in DNA repair, but also in gametogenesis, early embryo development, embryo implantation, and pregnancy maintenance [1,10]. Two common MTHFR polymorphisms, C677T and…”
Section: Introductionmentioning
confidence: 99%
“…Methylation is a first‐line biochemical process playing an important role in the transmission of life and essentially involved in DNA and histone modification. 5 Numerous studies have shown that dysregulation of methylation processes (histones and DNA) can result in cancer development. For instance, Botezatu et al 6 have reported that changes in DNA methylation can lead to the activation of typically silent genes or silencing of generally active genes.…”
Section: Introductionmentioning
confidence: 99%